CITRA PEREMPUAN DALAM IKLAN POLITIK PUAN "KEPAK SAYAP KEBHINEKAAN" - Panji Ariyanto; Meida N Afina; Abdul Ghoni; Amanda Khusna (Academica: Journal of Multidisciplinary Studies, 2021)
In terms of quantity, women are rarely represented in political advertisements. In line with that, studies on how female figures are imaged in political advertisements are minimal. This study aims to provide an understanding of how women (Puan Maharani) are imaged in the political advertisement "Kepak Sayap Kebhinekaan" through the point of view of Roland Barthes' semiotic study. This study uses a qualitative approach by utilizing semiotic analysis. In the political advertisement "Kepak Sayap Kebhinekaan", women, in this case, Puan Maharani, are portrayed as having power as political leaders. In addition, women are portrayed as leaders who are nationalists, revolutionaries, protectors, guardians of diversity and deserve respect. The red color and the kebaya as a sign in Puan Maharani's political advertisement also have a negative connotation, namely opening up the perspective of female leaders with a communist stigma and lack of Islam. Â  Keywords: Political Advertisement; Representation; Woman Â